The influences of geological formations on water flow in wells in the municipality of Teófilo Otoni (International Journal of Geoscience, Engineering and Technology, 2020)
The present work had as main objective to associate the water flow rates found in tubular wells with the geological formations in the municipality of Teófilo Otoni in Brazil. This study focused on the identification of lithological formation at the well sites and whether the presence or absence of water in them is influenced by them. For this, data were collected from all tubular wells registered in the Groundwater Information System (SIAGAS) in the study area. This system is a database with all available information about groundwater wells collected in Brazil. In total, 200 data were found in the system, 74 from tubular wells, 117 from spring, 7 from excavated wells (cacimba/cistern) and 2 from monitoring wells. However, only 53 wells identified in the fissural system in the study area had flow data, static and dynamic levels. Those wells that lacked information about geological formation were analyzed together with geological maps. The results achieved that the Tumiritinga, Tonalito São Vitor and Granito Criciúma formations obtained the best well flow averages after stabilization, respectively with the values of 19.78, 18.58 and 17.36 m³/h. Wells 55 and 63 had the highest flow rates. It was noted that both were close to small lagoons that may be contributing to the maintenance of their recharge.
Keywords: Tubular well; Underground water; Geological formation